2005
DOI: 10.1590/s1519-69842005000100010
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variation on heavy metal concentrations in the oyster Ostrea equestris on the northern coast of Rio de Janeiro State, Brazil

Abstract: Heavy metal (Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn) concentrations were determined by ICP-AES in Ostrea equestris from three beaches (Barra do Furado, Buena, and Ponta do Retiro) on the northern coast of Rio de Janeiro State. The average concentration was 0.8 +/- 0.18, 0.4 +/- 0.21, 58 +/- 25.6, 249 +/- 52.3, 11 +/- 1.31, 0.55 +/- 0.16, 0.13 +/- 0.11, and 1131 +/- 321 microg x g(-1) dry weight for Cd, Cr, Cu, Fe, Mn, Ni, Pb, and Zn respectively. Significant spatial variation (p < 0.05) between the samples areas o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 23 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…The high cadmium concentration of 6.1 mg kg -1 observed in small sized oysters during the months of September and October, in contrast to the relatively low concentrations observed in medium and large oysters, suggests that oysters in the medium and large size classes are sexually mature and have an efficient metabolism and detoxifying process (Connell et al 1999) to keep the concentration of metals relatively low. In contrast, Ferreira et al (2005) reported that the prior selection of the size of the individuals in the effect of size on heavy metal accumulations. However, individuals of the same size are not necessarily the same age and weight because of the irregular shape of the substrate to which they are attached; individuals can grow along a different axis from the longitudinal growing pattern expected.…”
Section: Resultsmentioning
confidence: 94%
“…The high cadmium concentration of 6.1 mg kg -1 observed in small sized oysters during the months of September and October, in contrast to the relatively low concentrations observed in medium and large oysters, suggests that oysters in the medium and large size classes are sexually mature and have an efficient metabolism and detoxifying process (Connell et al 1999) to keep the concentration of metals relatively low. In contrast, Ferreira et al (2005) reported that the prior selection of the size of the individuals in the effect of size on heavy metal accumulations. However, individuals of the same size are not necessarily the same age and weight because of the irregular shape of the substrate to which they are attached; individuals can grow along a different axis from the longitudinal growing pattern expected.…”
Section: Resultsmentioning
confidence: 94%
“…It has taken approximately 20 years for the zinc content in oysters to reach the 2016 and 2017 levels, 450 mg kg -1 , which are even lower than those observed in the northern part of Rio de Janeiro state. 30 Considering that the Cd concentration in oysters has decreased to 0.078 mg kg -1 during 2016 and 2017, it is possible to conclude that, based on these two elements, the oysters in Sepetiba Bay are again edible.…”
Section: Resultsmentioning
confidence: 99%
“…However, anthropogenic activities have altered the geochemical cycle, increasing environmental concern regarding these pollutants (Ferreira et al, 2005).…”
Section: Introductionmentioning
confidence: 99%